2005
DOI: 10.3171/spi.2005.2.4.0457
|View full text |Cite
|
Sign up to set email alerts
|

A three-dimensional collagen matrix as a suitable culture system for the comparison of cyclic strain and hydrostatic pressure effects on intervertebral disc cells

Abstract: Object. To study intervertebral disc cell mechanobiology, the authors developed experimental systems that allow the application of cyclic strain and intermittent hydrostatic pressure (IHP) on isolated disc cells under equal three-dimensional (3D) culture conditions. The purpose of the study was to characterize disc cell proliferation, viability, morphology, and gene expression in 3D collagen matrices. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
89
1
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 74 publications
(94 citation statements)
references
References 39 publications
3
89
1
1
Order By: Relevance
“…They were able to define a loading threshold of 0.2 MPa, reflecting homeostasis, which preserved tissue composition and found changes in the gene expression in case of under-or overshooting this load. In our own pilot study on human cells exposed to mechanical stimulation in a 3D collagen type-I gel, we have found nucleus and annulus cells to respond to cyclically applied HP at 0.25 MPa [12]. Changes in the gene expression showed anabolic tendencies, but the effects were relatively minor.…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations
“…They were able to define a loading threshold of 0.2 MPa, reflecting homeostasis, which preserved tissue composition and found changes in the gene expression in case of under-or overshooting this load. In our own pilot study on human cells exposed to mechanical stimulation in a 3D collagen type-I gel, we have found nucleus and annulus cells to respond to cyclically applied HP at 0.25 MPa [12]. Changes in the gene expression showed anabolic tendencies, but the effects were relatively minor.…”
Section: Introductionmentioning
confidence: 92%
“…Cell isolation and cell culture was conducted as previously described [12]. Briefly, cells were isolated by collagenase-pronase digestion from the nucleus pulposus of human disc biopsies from 18 donors (average age 39 ± 17) who underwent surgery because of disc herniation (for details of all patients see Table 1).…”
Section: Disc Cell Isolation and Preparation Of Cell Loaded Collagen mentioning
confidence: 99%
See 2 more Smart Citations
“…The requirements therefore are to provide a scaffold with adequate mechanical properties, which allows to culture suitable cells in it, for example, intervertebral disc cells or mesenchymal progentitor cells (MPCs). A recent study showed that a threedimensional collagen matrix might suitably serve as scaffold for cell seeding, that could be used to serve as a nucleus replacement [16]. It could be shown that these cells were able to proliferate and that cell viability was still 92% after 4 weeks.…”
Section: Introductionmentioning
confidence: 99%